Simulation of laser-induced tunnel ionization based on a curved waveguide - Arnon Ben Levy; Amir Hen; Merav Kahn; Yoad Aharon; Tamar Levin; Noa Mazurski; Uriel Levy; Gilad Marcus (Scientific Reports, 2023)
Abstract The problem of tunneling ionization and the associated questions of how long it takes for an electron to tunnel through the barrier, and what the tunneling rate has fascinated scientists for almost a century. In strong field physics, tunnel ionization plays an important role, and accurate knowledge of the time-dependent tunnel rate is of paramount importance. The Keldysh theory and other more advanced related theories are often used, but their accuracy is still controversial. In previous work, we suggested using a curved waveguide as a quantum simulator to simulate the tunnel ionization process. Here we implemented for the first time such a curved waveguide and observed the simulated tunneling ionization process. We compare our results with the theory.